The answer is
B. -2 and 3
Step-by-step explanation :
Given the expression
x²- 5x + 6 = 0
Firstly we need to find two numbers that when multiplied will give us the constant term 6, and when added will give us the 2nd term 5
These numbers are 3 and 2
Substituting 2x +3x for 5x
x²- (2x+3x)+ 6 = 0
x²-2x-3x+6=0
(x²-2x)-(3x+6)=0
Factoring we have
x(x-2)-3(x-2)=0
x-3=0, x-2=0
x=3, x= 2
You can take the log of the left and right hand side, and then apply the <span>logarithm rules:
log(a</span>ˣ) = x·log(a)
log(ab) = log(a) + log(b)
log(9^(x-1) * 2^(2x+2)) = log(6^(3x))
log(9^(x-1)) + log(2^(2x+2)) = 3x log(6)
(x-1) log(9) + (2x+2) log(2) - 3x log(6) = 0
x(log9 + 2log2 - 3log6) = log9 - 2log2
x = (log9 - 2log2) / (log9 + 2log2 - 3log6)
simplifying by writing log9 = 2log3 and log6 = log2+log3
x= 2(log3 - log2) / (2log3 + 2log2 - 3log2 - 3log3) =
x= -2(log3 - log2) / (log3 + log2) = -2 log(3/2) / log(6)
So 6^x = 4/9
Answer:
for question 13
- 130
- 50
- 50
- 130
- 130
- 50
- 50
- 130
Step-by-step explanation:
for 14
x. 150
y. 15
z. 150
i cant say that this is totally correct but im taking a educated guess
Hi There!
----------------------------------
Question 2:
Obviously the right equation for this question is Point Slope Form.
Point Slope Form: y - y1 = m(x - x1)
y1 = -1
x1 = 3
m = 2
Question 2 Answer: y + 1 = 2(x - 3)
----------------------------------
Question 3:
Again use point slope form.
Find Slope:
7 - 1 = 6
-2 - 1 = -3
6/-3 = -2
Question 3 Answer: y - 1 = -2(x - 1)
----------------------------------
Hope This Helps :)